The World Bank Group’s Mission - To End Extreme Poverty - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim, President of the World Bank Group, discusses strategies to address inequality that even the poorest nations can adopt, whether through conditional cash transfers, connecting farmers to markets or rural electrification. The lesson is that inequality is not an unsolvable mystery. Pro-equality policies are not luxury goods and can work in any country. Economic growth must be more robust and more inclusive and human capital investments have to grow in size and effectiveness.